A dualband bandpass filter with tunable bandwidths for automotive radar and 5G millimeter-wave applications - Thierno Amadou Mouctar Balde; Franklin Manene; Franck Moukanda Mbango (Institute of Advanced Engineering and Science, 2022)
A compact dual wideband bandpass filter for automotive radar (AR) and 5G millimeter-wave (mmWave) applications with adjustable bandwidths is presented in this work. The filter is based on microstrip dual-mode edge-coupled stub-loaded resonators (SLR). The novelty of this configuration is that it allows independent control of the bandwidths which is not obvious for many reported SLR-based filters. To achieve an overall size of 1.23λ_g× 2.02λ_g, these resonators are coupled and bent int o U-shape, T-shape, and E-shape. The U-shaped resonator, based on a quarter-wavelength transmission line, is coupled to the T-shaped element which constitutes the main feed line to obtain the dual-band response. Having a symmetrical structure, the design i s studied using the even-odd mode analysis. The layout is made using the Ansys high-frequency structural simulator (HFSS) and fabricated on Rogers RO3010 with a thickness of 1.28 mm, a dielectric constant of 10.2, and a loss tangent of 0.0022. The measured bandwidths are 660 MHz and 880 MHz at central frequencies of 23.92 GHz and 28.38 GHz respectively. The measured insertion losses are less than 3.9 dB and the return losses are greater than 17 dB in both bands. A good agreement is obtained between simulate d and experimental results.